HUBUNGAN NEUROPATI OTONOM DAN RISIKO OBSTRUCTIVE SLEEP APNEA SYNDROME PADA PASIEN DIABETES MELLITUS TIPE 2 - Nushrotul Lailiyya,* Sobaryati,* Miftahurachman,* Marina* (NEURONA, 2017)
INTRODUCTION HIGH PREVALENCE 58 OF OBSTRUCTIVE SLEEP APNEA SYNDROME OSAS HAS BEEN REPORTED IN PATIENTS WITH TYPE 2 DIABETES MELLITUS T2DM THIS MOSTLY FOUND IN T2DM PATIENTS WITH OBESITY AND AUTONOMIC NEUROPATHY THAT IS WHY IT IS IMPORTANT TO KNOW THE FACTORS THAT INFLUENCE THE RISK OF OSAS FOR PREVENTION OF THE DISEASE